2015
DOI: 10.11138/gchir/2015.36.2.063
|View full text |Cite
|
Sign up to set email alerts
|

Papillary glioneuronal tumor: case report and review of literature

Abstract: Papillary glioneuronal tumor (PGNT) is a recently described central nervous system neoplasm that mostly occurs in the supratentorial system, adjacent to the lateral ventricles. Well-established examples of glioneuronal tumors include DNET (Dysembryoplastic NeuroEpithelial Tumor), ganglioglioma and desmoplastic infantile ganglioglioma. More recently recognized entities include rosette-forming tumor of fourth ventricle, rosette glioneuronal tumor (RGNT)/ glioneuronal tumor with neuropil-like islands and PGNT (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…On MRI, PGNT is frequently described as a well-demarcated mass with a cystic component, contrast enhancement, isointensity on T1-weighted and a predominant location in the periventricular area [22]. However, there is no pathognomonic radiographic appearance and in the review by Carangelo and colleagues, around 80 % of PGNT showed a ventricular association [3]. All our cases show a ventricular association, one is clearly intraventricular, similar to the case reported by Matyja and colleagues [23] and the two others, the tumor have a direct contact with the temporal ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On MRI, PGNT is frequently described as a well-demarcated mass with a cystic component, contrast enhancement, isointensity on T1-weighted and a predominant location in the periventricular area [22]. However, there is no pathognomonic radiographic appearance and in the review by Carangelo and colleagues, around 80 % of PGNT showed a ventricular association [3]. All our cases show a ventricular association, one is clearly intraventricular, similar to the case reported by Matyja and colleagues [23] and the two others, the tumor have a direct contact with the temporal ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…This tumor is rare, with approximately 70 cases reported in the last decade [3, 4]. Classifying PGNT is a challenge with a diagnosis generally based on neuroimaging and histology.…”
Section: Introductionmentioning
confidence: 99%
“…The present case, however, may question this clinical attitude as the tumor did enlarge during its 10 years of clinical course and the Ki-67 (MIB-1)-labeling index was 3%, which could be considered as borderline. Close to a hundred cases have been reported in the English literature [ 4 , 7 , 8 ]. Mean age at diagnosis is 25.7 years (range: 4–75 years); 75% have been <30 years old [ 4 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Close to a hundred cases have been reported in the English literature [ 4 , 7 , 8 ]. Mean age at diagnosis is 25.7 years (range: 4–75 years); 75% have been <30 years old [ 4 , 7 , 8 ]. The patient in the present case was relatively old compared to the mean age for this pathology and MIB-1 was borderline (3%) but the tumor was considered as a WHO grade I tumor as histological findings were compatible to WHO grade I PGNT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous limitations in diagnosis were related to limited ability to elicit radiographic differences, scant material for pathological analysis and the overall rarity of glioneuronal tumors. Ganglioglioma, paraganglioma, central neurocytoma and DNET have been reported on for some time (Figure 1) (1)(2)(3)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). RGNT (39)(40)(41), PGNT (42,43) and GNTNI (44) were added to the WHO classification in 2007 (1).…”
Section: Pathological Molecular and Imaging Featuresmentioning
confidence: 99%